Pulmonary Rehabilitation Improves Self-Management Ability in Subjects With Obstructive Lung Disease. - Janssen, Steffi M. J.; Vliet Vlieland, Thea P. M.; Volker, Gerard; Spruit, Martijn A.; Abbink, Jannie J. (Respiratory Care, 2021)
BACKGROUND: Optimizing self-management is a key element in multidisciplinary pulmonary rehabilitation in patients with asthma or COPD. This observational study aimed to investigate the changes in self-management following pulmonary rehabilitation in subjects with chronic lung disease. METHODS: Data were prospectively and routinely gathered at initial assessment and discharge in subjects taking part in a 12-week multidisciplinary out-patient pulmonary rehabilitation program. Measures of self-management included the Patient Activation Measure (PAM), the Health Education Impact Questionnaire (HEIQ) (8 subscales), a Self-Efficacy Questionnaire (2 subscales), the Lung Information Needs Questionnaire (LINQ), and the Health Literacy Questionnaire (HLQ) (9 subscales). Mean differences with 95% CI and effect sizes were computed. RESULTS: A total of 70 subjects (62.9% women) were included, with a median age of 63.5 y; most of the subjects had been diagnosed with COPD (77%). Between admission and discharge, all measures of self-management increased significantly except for the HEIQ subscales of constructive attitudes and approaches, social integration and support, and health services navigation; and the HLQ subscale of social support for health. The largest improvements (effect size > 0.55) were seen for the PAM (0.57); the HEIQ subscales of health-directed behavior (0.71), self-monitoring and insight (0.62), and skill and technique acquisition (1.00); the HLQ subscales of having sufficient information to manage my health (1.21) and actively managing my health (0.66); and the LINQ (1.85). CONLCUSIONS: Self-management, including activation, improved significantly in subjects with asthma or COPD who took part in a multidisciplinary pulmonary rehabilitation program.